An Analytical Study of Pakistani Law Regarding Assurance of Halal Production and Consumption - Shah, Dr. Noor Wali; Akhtar, Dr. Nisar (Al-Irfan, 2023)
The term Halaal is booming day by day. The entire world is in competition to boost it in order to add in the economy of their countries. Pakistan is an Islamic country and has designed its constitution in the light of Shariah. Halaal laws were first adopted by Thailand a non-Islamic country and Malaysia. After the formation of PSQCA in 1996 Shariah Standards for slaughtering were drafted by government. Then they were reviewed in 2010. Since then more than ten halal standards are approved by NSC PSQCA. In 2015 a bill by the name “Pakistan Halaal Authority PHA 2015” was approved by National Assembly and Senate, and now it has started working for the last some years. In this paper first we will review local laws regarding food before introduction of the term Halaal in Pakistan and then will have a detail glance on Pakistani laws regarding Halaal food from 1996 till date. We will discuss the status of Halaal standards finalized by Halaal food technical and National committees PSQCA, the status of various government bodies working for Halaal, acts and laws approved by Government in the field of Halaal and then will give some recommendations to the government in the light of research.